Personality as an antecedent of work-family conflict : a variable- and person-centred approach - Omrawo, Charlene (Organisational Psychology, 2015)
This study examined the relationship between personality and work-family conflict amongst working fathers in South Africa. Two conceptual approaches to personality were employed: a variable-centred approach using the Big-Five personality dimensions (Costa & McCrae, 1992) and a person-centred approach using Asendorpf and Aken's personality prototypes (1999). Cross-sectional survey data were collected from working fathers in a variety of South African organisations (N = 237). Scale portability and robustness of the work-family conflict and personality scale was established through exploratory factor analysis. Hierarchical regression analysis showed that Neuroticism explained significant variance in work-to-family conflict and that Conscientiousness, Neuroticism and Openness to Experience explained significant variance in family-to-work conflict. Cluster analysis confirmed the personality prototypes, Overcontrollers, Undercontrollers and Resilients in this sample. Analysis of Variance results showed no difference in experiences of work-to-family conflict across Resilients, Overcontrollers and Undercontrollers. However, results showed that Resilients experienced less family-to-work conflict than Undercontrollers. Implications for theory and practice are discussed. This study examined the relationship between personality and work-family conflict amongst working fathers in South Africa. Two conceptual approaches to personality were employed: a variable-centred approach using the Big-Five personality dimensions (Costa & McCrae, 1992) and a person-centred approach using Asendorpf and Aken's personality prototypes (1999). Cross-sectional survey data were collected from working fathers in a variety of South African organisations (N = 237). Scale portability and robustness of the work-family conflict and personality scale was established through exploratory factor analysis. Hierarchical regression analysis showed that Neuroticism explained significant variance in work-to-family conflict and that Conscientiousness, Neuroticism and Openness to Experience explained significant variance in family-to-work conflict. Cluster analysis confirmed the personality prototypes, Overcontrollers, Undercontrollers and Resilients in this sample. Analysis of Variance results showed no difference in experiences of work-to-family conflict across Resilients, Overcontrollers and Undercontrollers. However, results showed that Resilients experienced less family-to-work conflict than Undercontrollers. Implications for theory and practice are discussed.